Optimal Combination of Chest Compression Depth and Rate in Virtual Reality Resuscitation Training: A Post Hoc Analysis of the Randomized Lowlands Saves Lives Trial - Joris Nas; Jos Thannhauser; Robert‐Jan M. van Geuns; Niels van Royen; Judith L. Bonnes; Marc A. Brouwer (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Dissemination of cardiopulmonary resuscitation (CPR) skills is essential for cardiac arrest survival. Virtual reality (VR)‐training methods are low cost and easily available, but to meet depth requirements adaptations are required, as confirmed in a recent randomized study on currently prevailing CPR quality criteria. Recently, the promising clinical performance of new CPR quality criteria was demonstrated, based on the optimal combination of compression depth and rate. We now study compliance with these newly proposed CPR quality criteria. Methods and Results Post hoc analysis of a randomized trial compared standardized 20‐minute face‐to‐face CPR training with VR training using the Lifesaver VR smartphone application. During a posttraining test, compression depth and rate were measured using CPR mannequins. We assessed compliance with the newly proposed CPR criteria, that is, compression rate within ±20% of 107/minute and depth within ±20% of 47 mm. We studied 352 participants, age 26 (22–31) years, 56% female, and 15% with CPR training ≤2 years. Among VR‐trained participants, there was a statistically significant difference between the proportions complying with newly proposed versus the currently prevailing quality criteria (52% versus 23%, P<0.001). The difference in proportions complying with rate requirements was statistically significant (96% for the new versus 50% for current criteria, P<0.001), whereas there was no significant difference with regard to the depth requirements (55% versus 51%, P=0.45). Conclusions Lifesaver VR training, although previously found to be inferior to face‐to‐face training, may lead to CPR quality compliant with recently proposed, new quality criteria. If the prognostic importance of these new criteria is confirmed in additional studies, Lifesaver VR in its current form would be an easily available vector to disseminate CPR skills.